THE ROLE PLAY TECHNIQUE TO IMPROVEMENT THE STUDENT’S SPEAKING SKILL FOR THE 8th GRADE STUDENTS AT SMPN 1 BLANGPIDIE ACEH BARAT DAYA - Nasihah, Isti Qomaton; Moetia, Meristika (FKIP Unismuh Makassar, 2024)
The research was conducted to effectiveness of role-play in improving students' speaking skills SMPN 1 Blangpidie Aceh Barat Daya, and increasing their motivation by utilizing this role-play technique. This research was influenced by students' perception that speaking skills are one of the most challenging aspects of learning English. The study employed a quantitative descriptive research method. Data analysis was conducted using a paired t-test. The results indicate that students have benefited from using the role play technique. The success of using role play in the classroom was obtained from exposure to real data statistical calculation of t-test 4.37 and t-table value 2. 093. Roleplay improved student motivation and is also effective in improving students' speaking skills in class.